Alternantele vocalice neregulate din flexiunea verbală românească - Cychnerski, Tomasz (Studia Romanica Posnaniensia, 2006)
This paper, that is part of a bigger research project concerning the morphonology of the standard contemporary Romanian, concentrates on the irregular vocalic alternations in the Romanian verbal inflection. Seventeen of the twenty-four possible alternations are irregular. The context in which the alternant members appear is analysed precisely according to the units that follow and precede them. The analysis shows that six of all the alternations are only morphologically conditioned. The e ~ a alternation acquires the categorial function in the structure of three verbs.